Valued living among veterans in breath-based meditation treatment or cognitive processing therapy for posttraumatic stress disorder: Exploratory outcome of a randomized controlled trial - R Jay Schulz-Heik; Laura C Lazzeroni; Beatriz Hernandez; Timothy J Avery; Danielle C Mathersul; Julia S Tang; Emily Hugo; Peter J Bayley (SAGE Publishing, 2022)
Background Valued living is the extent to which an individual's behavior is consistent with what they believe is important or good. It is unknown whether many complementary and integrative treatments and psychotherapies for posttraumatic stress disorder enhance valued living, and for whom. Objectives Measure within- and between-group changes in valued living in Veterans who completed cognitive processing therapy (CPT) and sudarshan kriya yoga (SKY) for posttraumatic stress disorder (PTSD); evaluate moderators of improvement. Methods Participants with clinically significant symptoms of PTSD were assigned to CPT, a first line, evidence-based psychotherapy for PTSD or SKY, an emerging breath-based meditation with strong preliminary empirical support in a parallel-groups randomized controlled trial at a single Veterans Affairs healthcare center. The Valuing Questionnaire subscales for progress in valued living (VQ-P) and obstruction in valued living (VQ-O) were exploratory outcome measures. Assessors were blind to treatment assignment. Results 59 participants completed treatment (29 CPT, 30 SKY). Participants in the CPT group improved from baseline to end of treatment in both VQ-Progress ( d= 0.55, p= 0.02) and VQ-Obstruction ( d= -0.51, p= 0.03), while the SKY group did not improve on either subscale ( d= 0.08, p= 0.69; d= 0.00, p= 1.00). However, differences between treatments were not statistically significant ( p= 0.16, 0.11, respectively). Participants reporting less valued living and more depression symptoms at baseline reported greater improvements in valued living following treatment. Conclusion CPT may have a positive effect on valued living. Individuals lower in valued living and with more depression may derive relatively more benefit.